THE MODIFICATION OF TITANIUM DIOXIDE (TiO2) CRYSTAL STRUCTURE, OPTICAL PROPERTIES AND PHOTOCATALYTIC PERFORMANCE TOWARDS THE DEGRADATION OF REMAZOL BRILLIANT BLUE DYE - MOHD FOAD, NUR SYAHIDATUL INSYIRAH (2024)
Titanium dioxide (TiO2) nanomaterial has been extensively studied and reported as the prominent photocatalyst especially towards environmental remediation. The high stability, non-toxicity and cost effectiveness promotes TiO2 as an ideal photocatalyst to be employed in the degradation of organic pollutant. However, its large band gap of 3.2 eV has hindered its efficiency in the visible light region. In this study, TiO2 was synthesized via one-pot reflux condensation and hydrothermal methods. Evaluation on the effect of heating duration (18-48 hours), heating temperature (100-200 ℃), and addition of dopant and co-dopant (fluorine, chlorine and nitrogen) towards modifying the optical and morphological properties as well as the crystal structure are thoroughly evaluated. The findings from this study exposed that the incorporation of HF as dopant manage to enhance the optical properties by reduction of band gap to 2.78 eV, thus improving the visible light responsiveness. The study further evaluates the functionalities of HCl towards the formation of a mid-gap state, hence improving the anatase TiO2 optical properties. Interestingly, co-doping of TiO2 with HF and HCl also promotes the formation of anatase TiO2 with reduction of band gap to 2.85 eV which also leads to the increment of photocatalytic performance of TiO2. The effect of {001} facet percentage also had been investigated which shows sample F-TiO2 (R) possesses the enhancement of {001} facet by 21.9 %. Besides, the employment of nitrogen precursors (urea and nitric acid) also had shown to enhance the carrier separation between photoexcited electrons and holes. In this study, the photocatalytic activity of F/Cl-TiO2 (R) and N-TiO2/urea (R) shows improvement in the degradation of Remazol Brilliant Blue. F/Cl-TiO2 (R) depicts the highest degradation by 86.38% and 37.26%, while N-TiO2/urea+HNO3 (R) shows degradation by 84.55% and 34.0% for broad spectrum and blue light, respectively. The findings show that TiO2 synthesized via reflux-condensation method and co-doped with F and Cl plays an important role in modifying the properties and dominate in degradation of Remazol Brilliant Blue under broad spectrum and blue light irradiation.